Analysis of the Needs for Development of Kahoot Game-Based Learning Media - Enyea Winanda Hardianti (CV. Media Inti Teknologi, 2023)
The use of technology in learning by using IT advances is intended to make learning activities more effective, one of which is the use of Kahoot media. This study aims to analyze the development of Kahoot game-based learning media so that it can increase student motivation and learning outcomes. The research data was taken from informatics teachers and class VII students at SMPN 2 Bengkulu Selatan. The data analysis technique used is qualitative and quantitative sequentially. Data collection techniques used are questionnaires and written tests. The development model used is 4D, consisting of 4 main stages, namely define, design, development, and disseminate. In this study, the questionnaire respondents consisted of 32 students and 2 Informatics teachers at SMPN 2 Bengkulu Selatan. The data distributed is in the form of the feasibility of the content of the material which is validated by material experts 83%